Effect of long-term beta-blocker treatment following myocardial infarction among stable, optimally treated patients without heart failure in the reperfusion era: a Danish, nationwide cohort study. (11th January 2021) - Holt, Anders; Blanche, Paul; Zareini, Bochra; Rajan, Deepthi; El-Sheikh, Mohammed; Schjerning, Anne-Marie; Schou, Morten; Torp-Pedersen, Christian; McGettigan, Patricia; Gislason, Gunnar H; Lamberts, Morten
Abstract: Aims: We aimed to investigate the long-term cardio-protective effect associated with beta-blocker (BB) treatment in stable, optimally treated myocardial infarction (MI) patients without heart failure (HF). Methods and results: Using nationwide registries, we included patients with first-time MI undergoing coronary angiography (CAG) or percutaneous coronary intervention (PCI) during admission and treated with both acetyl-salicylic acid and statins post-discharge between 2003 and 2018. Patients with prior history of MI, prior BB use, or any alternative indication or contraindication for BB treatment were excluded. Follow-up began 3 months following discharge in patients alive, free of cardiovascular (CV) events or procedures. Primary outcomes were CV death, recurrent MI, and a composite outcome of CV events. We used adjusted logistic regression and reported standardized absolute risks and differences (ARD) 3 years after MI. Overall, 30 177 stable, optimally treated MI patients were included (58% acute PCI, 26% sub-acute PCI, 16% CAG without intervention). At baseline, 82% of patients were on BB treatment (median age 61 years, 75% male) and 18% were not (median age 62 years, 68% male). BB treatment was associated with a similar risk of CV death, recurrent MI, and the composite outcome of CV events compared with no BB treatment [ARD (95% confidence intervals)] correspondingly; 0.1% (−0.3% to 0.5%), 0.2% (−0.7% to 1.2%), and 1.2% (−0.2% to 2.7%). Conclusions: In this nationwide cohort study of stable, optimally treated MI patients without HF, we found no long-term effect of BB treatment on CV prognosis following the patients from 3 months to 3 years after MI admission. Graphical Abstract: